Quantitative analysis of cerebral carotid CTA image quality and radiation dose at low kv and standard kv variations using bolus tracking technique - Olivia Ganna; Akhirida Putri; Wenda Anastasia; Suherman Hardi Saputro; Mira Maya Kumala; Nurwahyu; Purwanto; Muhammad Saifur Rohmad (Edukasi Ilmiah Indonesia, 2026)
Introduction: Computed Tomography Angiography (CTA) of the cerebral carotid arteries is a key non-invasive modality for evaluating vascular abnormalities. Image quality and radiation dose are strongly influenced by tube voltage (kVp). Lower tube voltage may enhance iodine attenuation and reduce radiation exposure. This study aimed to compare vascular image quality and radiation dose between low tube voltage (70 kVp) and standard tube voltage (100 kVp) in cerebral carotid CTA using bolus tracking. Research Methodology: A quantitative comparative retrospective study was conducted on 20 patients, divided into two groups: 70 kVp (n=10) and 100 kVp (n=10). Image quality was assessed using arterial enhancement (Hounsfield Unit, HU) and Signal-to-Noise Ratio (SNR) measured at the ascending aorta, common carotid artery, and middle cerebral artery using Region of Interest (ROI) analysis. Radiation dose parameters included CTDIvol and Dose Length Product (DLP). Data normality was tested using the Shapiro–Wilk, followed by the the Mann–Whitney and independent t-test for comparative analysis. Results: The 70 kVp protocol significantly increased arterial enhancement (e.g., ascending aorta: 697.36±81.06 HU vs 328.25±34.75 HU) and SNR (29.43±16.29 vs 15.68±7.95) compared to 100 kVp (p < 0.05). Radiation dose was substantially reduced, with CTDIvol decreasing from 8.08 mGy to 2.82 mGy and DLP from 284.66±10.92 mGy·cm to 102.12±3.08 mGy·cm (p < 0.05). Conclusion: Low tube voltage (70 kVp) significantly improves vascular image quality while reducing radiation dose in cerebral carotid CTA. This protocol supports radiation optimization principles and can be considered an effective alternative in clinical practice.